Configuration of the extra-renal venous system in relation to the left renal vein: A cadaveric study and new proposed classification. Issue 6 (December 2020) - Walker, Alexander; Slim, Naim; Nicholson, Michael; Brassett, Cecilia
Abstract: The advent of laparoscopic live-donor nephrectomy for renal transplantation has prompted the need to define the precise anatomical relations of the left renal vein (LRV) and its tributaries. The left kidney is preferred as the greater length of the LRV facilitates implantation in the recipient. While previous studies have described variations in the LRV system, the connections between the left ascending lumbar vein (LALV) and LRV tributaries have been less well-defined. This study aims to further characterise the LALV and proposes a novel classification for its relation to other veins. Dissection of the LRV system, including the left suprarenal vein (LSV), left gonadal vein (LGV) and LALV, was performed in 38 cadavers. Their drainage points into the LRV were recorded, and measurements taken of the distances from these points to the junction of the LRV and inferior vena cava (IVC). The position of the LRV in relation to the aorta was anterior in 35 cases (92%), entirely posterior in 1 case (3%), and circumaortic in 2 cases (5%). Duplication of the LSV and LGV occurred in 6 (16%) and 10 (27%) cases respectively. A direct posterior connection between the LALV and LRV was identified in 32 (86%) cases. The drainage point of the LALV into the LRV lay between the IVC and LGV in 8 (25%) cases. In 20 cases (63%), the drainage points of the LALV and LGV were equidistant from the IVC; and in 5 cases (16%), those of the LALV and posterior branch of the LRV were equidistant from the IVC. In these two groups, the vessels shared a confluent trunk in 10 and 4 cases respectively. In 3 cases, connections were observed between all three vessels (LALV, LGV and posterior branch of LRV). No confluence trunk was shared by the LALV and LSV. These results confirm the high incidence of communicating LALVs, which represent a potentially troublesome source of operative bleeding if unrecognised. Confluent venous trunks may also present difficulties during vessel ligation prior to nephrectomy. It is suggested that a novel classification of the relation of the LALV based on these findings may assist in surgical planning and reduce complications.